The Relationship between Manufacturing Company Values and Corporate Social Responsibility - Mandasari, Virginia; Kirana, Nanda Wahyu Indah (Nusantara Science and Technology Proceedings, 2023)
Corporate social responsibility (CSR) has recently drawn more interest from academic economists and managers working in the real world. The implementation of corporate social responsibility allows you to report economic, social, and environmental activities to stakeholders, which can raise the value of your organization. This can build trust and foster positive relationships with stakeholders, easing their concerns about the future. Investors and customers in the market tend to place more focus on and attention to corporate social responsibility (CSR) conduct in organizations, and many of these companies pay attention to consumer welfare, environmental concerns, and environmentally friendly production (Fukuda & Ouchida, 2020). In addition to increasing sales and consumer loyalty, better quality and productivity, increased ability to retain employees, and increased access to capital markets, corporate social responsibility can enhance brand image and reputation. These effects can all increase company value.